Cannabinoids and Glucocorticoids in the Basolateral Amygdala Modulate Hippocampal–Accumbens Plasticity After Stress - Segev, Amir (Neuropsychopharmacology, 2016)
Acute stress results in release of glucocorticoids, which are potent modulators of learning and plasticity. This process is presumably mediated by the basolateral amygdala (BLA) where cannabinoids CB1 receptors have a key role in regulating the hypothalamic–pituitary–adrenal (HPA) axis. Growing attention has been focused on nucleus accumbens (NAc) plasticity, which regulates mood and motivation. The NAc integrates affective and context-dependent input from the BLA and ventral subiculum (vSub), respectively. As our previous data suggest that the CB1/2 receptor agonist WIN55,212-2 (WIN) and glucocorticoid receptor (GR) antagonist RU-38486 (RU) can prevent the effects of stress on emotional memory, we examined whether intra-BLA WIN and RU can reverse the effects of acute stress on NAc plasticity. Bilateral, ipsilateral, and contralateral BLA administration of RU or WIN reversed the stress-induced impairment in vSub–NAc long-term potentiation (LTP) and the decrease in cAMP response element-binding protein (CREB) activity in the NAc. BLA CB1 receptors were found to mediate the preventing effects of WIN on plasticity, but not the preventing effects of RU, after stress. Inactivating the ipsilateral BLA, but not the contralateral BLA, impaired LTP. The possible mechanisms underlying the effects of BLA on NAc plasticity are discussed; the data suggest that BLA-induced changes in the NAc may be mediated through neural pathways in the brain's stress circuit rather than peripheral pathways. The results suggest that glucocorticoid and cannabinoid systems in the BLA can restore normal function of the NAc and hence may have a central role in the treatment of a variety of stress-related disorders.